Keuangan Negara Menurut al-Māwardī dalam al-Aḥkām al-Sulṭānīyah wa al-Walāyāt al-Dīnīyah dan Peluang Implementasinya di Indonesia - Rahmat Rahmat; Azwar Iskandar; Khaerul Aqbar (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
This article deals with the public finance from the perspective of Islamic law according to al-Māwardī in his al-Aḥkām al-Sulṭānīyah wa al-Walāyāt al-Dīnīyah, particularly in the government expenditure sector and supervision of public finance. This article tries to analyze opportunities and challenges in aplying the concept of public finance from Islamic perspective. Using library research method with multidisciplinary approaches, namely: legal, philosophical and sociological, this article reveals some findings. Fisrt, the public finance according to al-Māwardī is divided into two parts, namely the limited expenditure and unlimited expenditure. A limited government expenditure includes the expenditure from the source of zakat, ghanīmah and fay’, while unlimited expenditures are allocated to fund the government activities, such as routine, civil and military, development, subsidies and social welfare. Second, the supervision of the public finances, according to al-Māwardī is covered in the hisbah system, namely the amar makruf system that involves two parties, independent institutions created by the government and society. Third, the opportunity to enforce the financial concept based on Islamic law is open, because Islamic law has existed and become part of the source of positive or national law, and supported by the character of Islamic law itself which is fair or balanced between material (worldly) and spiritual interests and is dynamic. Fourth, there are challenges for the implementation of Islamic law in the field of public finance, such as the poor understanding of society to the teachings of Islam, the lack of religious norms in statutory products, weakness in the unity of Muslims, and the weak poor political will.